Neoclassical versus technological convergence: An empirical analysis applied to the Italian regions - Carluccio Bianchi; Mario Menegatti (Università degli Studi di Pavia, Dipartimento di Economia Politica e Metodi Quantitativi (EPMQ), 2005)
This paper tests for the existence of neoclassical and/or technological catching up between the Italian regions in the last three decades. The tests are performed by means of a modified b-convergence equation and of a model based on the decomposition of output growth. The results imply that while the neoclassical convergence mechanism occurred, the technological one failed. The paper also provides a possible explanation for these results and analyses their policy implications, suggesting that a complete convergence between the Italian regions may be achieved only by promoting technological transfers and by increasing research expenditure in backward regions.
Keywords: O41; O47; O49; 330; convergence; catching up; TFP; Italian regions; Entwicklungskonvergenz; Regionale Entwicklung; Technischer Fortschritt; Produktivität; Italien